2021
DOI: 10.1007/s40979-021-00088-4
|View full text |Cite
|
Sign up to set email alerts
|

International students’ knowledge and emotions related to academic integrity at Canadian postsecondary institutions

Abstract: This study investigated the knowledge of academic integrity and associated emotions of a small sample of international students studying at Canadian postsecondary institutions (n = 60) using survey methodology. Depending on the survey item, 25–60 participants provided responses. Many respondents appeared knowledgeable about academic integrity and misconduct and reported that expectations in their home countries and in Canada were similar. There was, however, disagreement on the concept of duplicate submission/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 42 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…In addition, this new research formula promotes a peer-assessment-oriented academic integrity testing approach in each item formulation [31][32][33][34][35][36] and complements encouragement as the latest indicator in measuring, assessing, and evaluating student academic integrity. The primary difference is the addition of encouraging factors in the construction of PAAIS-24 items, as has been recommended as an essential principle in training one's academic integrity [72][73][74][75][76]. Considering that in the latest learning trends, students are given more autonomy to develop their potential through peer-assessment, peer-assessment experiences can ideally shape students' academic integrity behavior while acting boldly to promote various proactive behaviors that support the development of peers' academic performance.…”
Section: -2-discussionmentioning
confidence: 99%
“…In addition, this new research formula promotes a peer-assessment-oriented academic integrity testing approach in each item formulation [31][32][33][34][35][36] and complements encouragement as the latest indicator in measuring, assessing, and evaluating student academic integrity. The primary difference is the addition of encouraging factors in the construction of PAAIS-24 items, as has been recommended as an essential principle in training one's academic integrity [72][73][74][75][76]. Considering that in the latest learning trends, students are given more autonomy to develop their potential through peer-assessment, peer-assessment experiences can ideally shape students' academic integrity behavior while acting boldly to promote various proactive behaviors that support the development of peers' academic performance.…”
Section: -2-discussionmentioning
confidence: 99%
“…These include "lack of support from administration (20% faculty, 16% TAs); lack of time to pursue suspected cases (20% faculty, 13% TAs); and the trivial nature of the offence (20% faculty, 24% TAs)" Christensen Hughes & McCabe, 2006, p. 12. Fifteen years later, when another study was conducted at Canadian universities that focused explicitly on international students, researchers similarly found that students were unsure of academic integrity concepts, with particular difficulties comprehending the topics of self-plagiarism and contract cheating (Sanni-Anibire et al, 2021). Yet another study at a Canadian university found that approximately half of students believed both that their instructors were more concerned with cheating, and that their peers committed more academic misconduct during the sudden shift to remote learning during the COVID-19 pandemic (Stoesz et al, 2023).…”
Section: (P 19)mentioning
confidence: 99%
“…A participant brings to the survey unique individual experiences and diverse cultural understandings of academic integrity and stress which checklists cannot capture. Previous research has pointed to the importance of considering international students’ knowledge and emotions related to academic integrity so that institutions may better respond to the challenges and supports of these students (Sanni-Anibire et al, 2021 ). Similarly, stressor checklists fail to capture individual perceptions of the severity of stress and assume all stressors produce negative consequences equally (Anderson et al, 2021 ).…”
Section: Limitationsmentioning
confidence: 99%